2020
DOI: 10.3390/genes11080895
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coilin Nonsynonymous SNP Variants E121K and V145I on Cell Growth and Cajal Body Formation: The First Characterization

Abstract: Coilin is the main component of Cajal body (CB), a membraneless organelle that is involved in the biogenesis of ribonucleoproteins and telomerase, cell cycle, and cell growth. The disruption of CBs is linked to neurodegenerative diseases and potentially cancers. The coilin gene (COIL) contains two nonsynonymous SNPs: rs116022828 (E121K) and rs61731978 (V145I). Here, we investigated for the first time the functional impacts of these coilin SNPs on CB formation, coilin subcellular localization, microtubule forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…CBs mediate small nuclear and nucleolar ribonucleoproteins and telomerase assembly and modification. CBs are enriched in transcriptionally active and or with high splicing demands, such as cancer cells (55). Our analysis indicates significant deregulation of several pathways associated with CBs in GBM cluster 3 (high ERa and ERb).…”
Section: Discussionmentioning
confidence: 70%
“…CBs mediate small nuclear and nucleolar ribonucleoproteins and telomerase assembly and modification. CBs are enriched in transcriptionally active and or with high splicing demands, such as cancer cells (55). Our analysis indicates significant deregulation of several pathways associated with CBs in GBM cluster 3 (high ERa and ERb).…”
Section: Discussionmentioning
confidence: 70%
“…Studies have shown that single-point mutations, including SNPs, on a single gene can cause abnormal functions of the protein and lead to human diseases [ 25 , 26 , 27 ]. Several mutations in the ZIP8 have been implicated in the occurrence of diseases related to the dysregulation of ion homeostasis [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another membrane-less organelle that formed via liquid phase separation is the Cajal body with coilin protein as scaffold protein. Cajal bodies are involved in the cell cycle, cell proliferation, ribonucleoprotein, and telomerase production (66). A recent study shows that the pseudogenes of coilin, coilp1 is accumulated in the nucleus, with strong accumulation in the nucleolus.…”
Section: Role Of Pseudogenes In Llpsmentioning
confidence: 99%